2010
DOI: 10.1074/jbc.m109.090506
|View full text |Cite
|
Sign up to set email alerts
|

Glutathione Transport Is a Unique Function of the ATP-binding Cassette Protein ABCG2

Abstract: Glutathione (GSH) transport is vital for maintenance of intracellular and extracellular redox balance. Only a few human proteins have been identified as transporters of GSH, glutathione disulfide (GSSG) and/or GSH conjugates (GS-X). Human epithelial MDA1586, A549, H1975, H460, HN4, and H157 cell lines were exposed to 2,5-dihydroxychalcone, which induces a GSH efflux response. A real-time gene superarray for 84 proteins found in families that have a known role in GSH, GSSG, and/or GS-X transport was employed to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
60
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(71 citation statements)
references
References 47 publications
(31 reference statements)
5
60
2
Order By: Relevance
“…Decreased levels of GSH have been observed in MDCKII cells overexpressing human ABCG2/BCRP (44). Additionally, BCRP overexpression in HN4 cells was observed to increase extracellular GSH levels (45). However, measurement of GSH transport in membrane vesicles indicated that BCRP does not catalyze any significant GSH transport (46).…”
Section: Resultsmentioning
confidence: 99%
“…Decreased levels of GSH have been observed in MDCKII cells overexpressing human ABCG2/BCRP (44). Additionally, BCRP overexpression in HN4 cells was observed to increase extracellular GSH levels (45). However, measurement of GSH transport in membrane vesicles indicated that BCRP does not catalyze any significant GSH transport (46).…”
Section: Resultsmentioning
confidence: 99%
“…Thus, the genetic redundancy between trxr-1 and gsr-1, and the observation that GSH can reduce disulfides in the cuticle, suggests that TRXR-1 and GSR-1 might act in molting by increasing GSH concentrations at the expense of GSSG. GSH can be exported from cells by certain proteins in the ATP-binding cassette (ABC) family, including ABCG2 (35), and thus could potentially exert its moltingpromoting functions extracellularly (e.g., together with secreted glutaredoxins). However, other models are also consistent with our results.…”
Section: Discussionmentioning
confidence: 99%
“…In the previous studies, ABCG2 was reported to transport glutathione, an important endogenous antioxidant. 23 In fact, in WT mice, glutathione peroxidase was highly upregulated in the early phase after TAC ( Figure 3D). Thus, we hypothesized that glutathione might be one of the key players in antioxidant response in the early phase during pressure overload.…”
Section: Abcg2 Regulates Extracellular Concentrations Of Glutathione mentioning
confidence: 99%